Amino sugars and their glycosides - Hindle, N; Fleet, G; Hindle, Neil A. (1995)
﻿ This thesis describes approaches to the transformation of simple carbohydrates into a polyhydroxylated pyrrolidine and the formation of its glucosides. Chapter one describes the synthesis of the naturally occurring pyrrolidine 2,5-dideoxy-2,5-imino-D-mannitol. Synthesised from di-O-isopropylidene-D-glucose, the key steps are the introduction of nitrogen at C-5 with retention of configuration. Then cyclisation of the nitrogen onto the C-2 position with inversion to form the pyrrolidine ring. Reduction of the aldehyde furnished the polyhydroxylated heterocycle in 3.4% yield over 16 steps. The synthetic compound matched the naturally occurring compound in all respects. Chapter two contains a review of commonly used glycosylation methods. It also describes the glycosylation of di-O-isopropylidene-α-D-glucose as a model system comparing the Koenig-Knorr method to the trichloroacetimidate method using several reaction conditions. Glycosylation of 2,5-dideoxy-2,5-imino-D-mannitol was carried out using the trichloroacetimidate method to synthese all four glucosides. Boron trifluoride etherate and trimethylsilyl trifluoromethanesulphonate were used as catalysts in dichloromethane, diethyl ether and acetonitrile under strictly anhydrous conditions. All four glucosides were prepared 1-O-(αβ-D-glucopyranosyl)-2,5-dideoxy-2,5-imino-D-mannitol and 3-O-(αβ-D-glucopyranosyl)-2,5-dideoxy-2,5-imino-D-mannitol. Biological screening carried out against a wide range of glycosidases and glycosyl transferases indicated that the glucosides showed little inhibition in comparison to 2,5-dideoxy-2,5-imino-D-mannitol. Chapter three describes the isolation and identification of 1-O-(β-D-glucopyranosyl)- 2,5-dideoxy-2,5-imino-D-mannitol from Nephthytis poisonii N.E.Br. a member of the Araceae family found in tropical Africa. Identification was made by comparison with the previously synthesised glucosides of 2,5-dideoxy-2,5-imino-Dmannitol. Investigations of Hyacinthoides non-scriptus (L.) chouard ex Rothm are also discussed. Chapter four describes the synthesis of a diazidolactone that could be used to form a 1,5 disubstituted tetrazole. This would have a second nitrogen functionality in the molecule allowing the possibility of the inclusion of the tetrazole into a peptide sequence. The synthesis was carried out from L-gulono-1,4-lactone. An azido group was introduced selectively at C-2, this unexpectedly occurred with retention of configuration. A second azide was then introduced at C-5, this occurring with the more commonly observed inversion of configuration to afford the 2,5-diazido-2,5-dideoxy-D-manno-1,4-lactone.